Impeller diffuser interactions in high speed centrifugal compressors - He, Ning (Cranfield University, 2001)
In the current research work, a computational analysis of a high-speed centrifugal compressor stage for turbocharger applications is presented. A detailed investigation about the interactions between backswept impeller and downstream vaneless and vaned diffusers is carried out. ' A unshrouded backswept impeller with splitters was combined with a vaneless diffuser or a number of different designs of vaned diffusers. The CFD solver CFX-TASCow was used. The three-dimensional Reynolds- Averaged Navier-Stokes equations are solved and a pressure correction method is employed to solve the system of equations. A steady simulation and analysis of the interactions between the impeller and the vaneless diffuser is carried out, emphasis is focused on the comparisons of the different interactions at different conditions regarding the flow structures at different radius ratios, effect of rotational speed, mass flow rate and impeller tip clearance. The predicted results were also compared with the available experimental results in terms of radial Velocity, tangential Velocity and flow angle. In general, the predicted results show a reasonable agreement with the experimental data. A steady state simulation and analysis regarding the interaction between the impeller and various vaned diffusers is carried out. For the interface between the rotational impeller outlet and the stationary vaned diffuser inlet, the stage averaging condition is used. A detailed comparison between the predicted and the available experimental data is performed in terms of static pressure rise, total pressure ratio, choking mass flow and efficiency characteristics, and very good agreement is accomplished. In addition, detailed flow distributions are compared, assessed and critically analysed, regarding different number of diffuser vanes, rotational speed, gap between the leading edge of the vaned diffuser and impeller tip, mass flow rate. Emphasis is focused on the steady state study of the effect of the number of diffuser vanes on the stage operating range. Further more, unsteady simulation and analysis regarding the interactions between backswept impeller and downstream vaned diffusers is carried out. In the unsteady simulation, a geometry scaling method is used to modify the diffuser geometry to the nearest integer pitch ratio while keeping the throat area, flow direction and area ratio unchanged in order to deal with the unequal pitch ratio problems which exist in the unsteady simulation. The unsteady investigation was undertaken regarding different number of diffuser vanes, rotational speed, gap between the leading edge of the vaned diffuser and impeller tip, mass flow rate and impeller tip clearance. The detailed interactions at different conditions are compared, assessed and analysed. The studies focus on the analyses of the effect of the different interactions on the stage operating range, peak efficiency, total pressure ratio, level of unsteadiness, flow structures, flow angle or incidence angle, etc. In addition, the' predicted results are compared with available experimental data and a quite good agreement is achieved although the geometry is scaled. On the other hand, a detailed investigation on the differences between the time averaged unsteady simulation results and steady simulation results was performed at different conditions. The comparisons were carried out regarding static pressure, total pressure, speed, flow angle (or incidence angle) and isentropic efficiency. The investigation confirms that unsteady simulation is still quite important, since some of the steady state simulation results are still not similar to the time averaged ones. Designers should take into account the influence of the unsteadiness on the flow fields when they employ the steady state model in the design process.